Mikroalbuminuria u zawodników gimnastyki sportowej - Szot, Z.; Matuszkiewicz, A. (Medycyna sportowa, 2000)
Nine well trained male gymnasts (sport Class III), aged 12-13 years, participated in the study. Albumin and creatinine were determined in urine samples collected 40 min after having performed 3 typical events: parallel bars exercise (73 elements), horizontal bar exercise (72 elements), or floor exercise (72 elements). Urinary albumin-to-creatinine ratio (UACR) was abnormally increased above 30 mg per g of creatinine in only one subject following the parallel bar event, in another subject following the horizontal bar event, and in two subjects following the free exercise event.